1981
DOI: 10.3109/01485018108987546
|View full text |Cite
|
Sign up to set email alerts
|

Glutamic-Oxalacetic Transaminase Leakage from Human Spermatozoa as an Indicator of Cryodamage

Abstract: The levels of extracellular glutamic-oxalacetic transaminase (GOT: EC 2.6.1. I ) activity have been measured in cell-free supernatants of human semen and of semen + cryoprotectant mixtures both before freezing by either cryostorage or quench-freezing regimes, and after subsequent thawing. The mean level of GOT activity in seminal plasma was 293 ( 2 15 sem) IUil at 37"C, this being 15 times the level in normal blood plasma. Seminal GOT is positively correlated (p Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Our results showed that the activity of ALT and AST was 76.75 ± 24.29 U/L and 439.31 ± 110.57 U/L, respectively; both of them were significantly higher than those in serum; in particular AST activity in seminal plasma was 13.71 times higher than that in serum, similar to the result reported by Hirsch et al [ 7 ], that is, ALT: 62.3 ± 25.7 IU/L and GOT: 412 ± 191.1 IU/L. Mortimer and Bramley [ 24 ] also reported that the level of AST in seminal plasma was about 15 times higher than that in serum. Moreover, as reported by Dhami and Kodagali [ 25 ], the activity of ALT was positively correlated with that of AST ( r = 0.514, P = 0.001).…”
Section: Discussionsupporting
confidence: 83%
“…Our results showed that the activity of ALT and AST was 76.75 ± 24.29 U/L and 439.31 ± 110.57 U/L, respectively; both of them were significantly higher than those in serum; in particular AST activity in seminal plasma was 13.71 times higher than that in serum, similar to the result reported by Hirsch et al [ 7 ], that is, ALT: 62.3 ± 25.7 IU/L and GOT: 412 ± 191.1 IU/L. Mortimer and Bramley [ 24 ] also reported that the level of AST in seminal plasma was about 15 times higher than that in serum. Moreover, as reported by Dhami and Kodagali [ 25 ], the activity of ALT was positively correlated with that of AST ( r = 0.514, P = 0.001).…”
Section: Discussionsupporting
confidence: 83%
“…In the former case, a significant diminution of glyceraldehyde 3phosphate dehydrogenase and total protein was recorded in human erythrocytes after thawing (Ballas 1981). In the second, significant changes in the activity of transaminase glutamic oxaloacetic, now known as aspartate aminotransferase (AST), were found in human (Mortimer & Bramley 1981) and chicken semen (Matsumoto et al 1985). Going a little further back, the deterioration of cell integrity due to cryopreservation, including alteration of proteins, was proposed by Karow and Webb (1965).…”
Section: Protein Damagementioning
confidence: 99%